A review of fifty tracheostomies - Eckstein, Herbert B.; Tombuloğlu, Lütfi (The Turkish Journal of Pediatrics, 1961)
Fifty consecutive cases of tracheostomy, performed over a period of two years in the Hacettepe Children’s Hospital, are analyzed, and it appears that in Turkey laryngo-tracheo-bronchitis is still the most frequent indication for this procedure. No less than twelve cases were suffering from diphtheria. In only nine cases was the tracheostomy performed for non-obstructive lesions. The difficulty which may be experienced in weaning a child from a tracheostomy tube is illustrated by two case reports.